Emerging open microfluidics for cell manipulation. (29th March 2021) - Zhang, Qiang; Feng, Shuo; Lin, Ling; Mao, Sifeng; Lin, Jin-Ming
Abstract : Emerging open microfluidics is a user-friendly, multifunctional and precise tool for cell manipulations. Basic principles, important applications, challenges and developing trends of the methodology are introduced in detail in this tutorial review. Abstract : Cell manipulation is the foundation of biochemical studies, which demands user-friendly, multifunctional and precise tools. Based on flow confinement principles, open microfluidics can control the movement of microscale liquid in open space. Every position of the circuit is accessible to external instruments, making it possible to perform precise treatment and analysis of cells at arbitrary target positions especially at the single-cell/sub-cell level. Benefiting from its unique superiority, various manipulations including patterned cell culture, 3D tissue modelling, localized chemical stimulation, online cellular factor analysis, single cell sampling, partial cell treatment, and subcellular free radical attack can be easily realized. In this tutorial review, we summarize two basic ideas to design open microfluidics: open microfluidic networks and probes. The principles of mainstream open microfluidic methods are explained, and their recent important applications are introduced. Challenges and developing trends of open microfluidics are also discussed.